Psychometric evaluation of the Australian Inventory of Family Strengths (AIFS) on rural Malay families in Malaysia - Arshat, Zarinah; Baharuddin, Rozumah (Universiti Putra Malaysia Press, 2014)
This study examines the psychometric properties of Australian Inventory of Family Strengths (AIFS) in a sample of 200 rural Malay families in Malaysia. The exploratory factor analysis of AIFS revealed 3-factor solution and were labelled as Shared Values, Togetherness and Respectful Communication. The overall scale had a high degree of internal consistency (a = 0.96). Results indicate that the three factors were moderately correlated. The validity of AIFS was also satisfying in terms of the actual data matching the expected correlation between family strengths measure and the variables of children's social competence and self-esteem. The results of this study imply that the construct of family strength and its measurement from the West can be helpful and applicable in understanding the characteristics of family strength of rural Malay families in Malaysia.